2016
DOI: 10.1017/s1041610216000806
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and efficacy of interventions for family caregivers of elderly persons with a mental disorder: a meta-analysis

Abstract: Comparative research for caregivers of elderly patients with mental disorders other than dementia is lacking. RCTs of interventions for family caregivers of dementia patients of the last decade show good acceptance among intervention participants, but there is still a need to improve the efficacy of these interventions. Individual customization of intervention components might enhance efficacy. More research is needed on the acceptance of telecommunication interventions for family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
2
15
0
3
Order By: Relevance
“…These findings are consistent with the results of some previous studies, including the study by Weinbrecht et al (2016), who indicated that family-centered interventions and counseling increased their acceptance of the client having a problem and, consequently, reduce the symptoms of the diseases (22). The findings are also consistent with the result of the study by Lee et al (2015), who showed that promoting acceptance for alcohol addicts improved them and reduced the relapse among them (23).…”
Section: Answering Questionssupporting
confidence: 92%
“…These findings are consistent with the results of some previous studies, including the study by Weinbrecht et al (2016), who indicated that family-centered interventions and counseling increased their acceptance of the client having a problem and, consequently, reduce the symptoms of the diseases (22). The findings are also consistent with the result of the study by Lee et al (2015), who showed that promoting acceptance for alcohol addicts improved them and reduced the relapse among them (23).…”
Section: Answering Questionssupporting
confidence: 92%
“…Subjective caregiving appraisals have mostly been investigated as outcomes in intervention studies . According to a meta‐analysis of randomized controlled trials targeting caregivers of persons with mental disorders involving dementia, most studies have been conducted in the USA and Europe—only four were conducted in Asia …”
Section: Introductionmentioning
confidence: 99%
“…7,11,12 According to a meta-analysis of randomized controlled trials targeting caregivers of persons with mental disorders involving dementia, most studies have been conducted in the USA and Europe-only four were conducted in Asia. 13 Longitudinal studies on the caregiving appraisal of caregivers of elderly persons with dementia have also been conducted in the USA and Europe. [14][15][16][17][18] These studies determined that caregiver burden leads to a greater risk for the need for long-term care and tends to decrease over time.…”
Section: Introductionmentioning
confidence: 99%
“…Being responsible for their own families, jobs, and a care recipient creates numerous challenges, leading to the caregiver feeling overwhelmed. Besides having no respite and support from family and friends, the majority of caregivers lack professional knowledge about the specific needs of a chronically ill person (e.g., administration of medications, knowledge about diet, helping with physical or occupational therapy; Ahmad, ; Weinbrecht, Rieckmann, & Renneberg, ).…”
Section: Current Understandingmentioning
confidence: 99%